2016
DOI: 10.1242/jcs.188466
|View full text |Cite
|
Sign up to set email alerts
|

The H3K4me3/2 histone demethylase RBR-2 controls axon guidance by repressing the actin-remodeling gene wsp-1

Abstract: The dynamic regulation of histone modifications is important for modulating transcriptional programs during development. Aberrant H3K4 methylation is associated with neurological disorders, but how the levels and the recognition of this modification affect specific neuronal processes is unclear. Here, we show that RBR-2, the sole homolog of the KDM5 family of H3K4me3/2 demethylases in Caenorhabditis elegans, ensures correct axon guidance by controlling the expression of the actin regulator wsp-1. Loss of rbr-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 43 publications
5
19
0
Order By: Relevance
“…The fact that rbr-2 and jmjd-1.2 share similar phenotypes when ablated, are both required during embryogenesis and bind H3K4me3 through their PHD domains, suggests that these histone demethylases might regulate axon guidance in a concerted manner. Indeed, we previously reported that rbr-2;jmjd-1.2 double mutants show similar levels of PVQ defects as the single mutants (Mariani et al, 2016), confirming that rbr-2 and jmjd-1.2 act in a common pathway regulating axon guidance. Altogether, these findings confirm that epigenetic factors are essential for the correct execution of developmental processes, providing novel insights into how neuronal development is achieved.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…The fact that rbr-2 and jmjd-1.2 share similar phenotypes when ablated, are both required during embryogenesis and bind H3K4me3 through their PHD domains, suggests that these histone demethylases might regulate axon guidance in a concerted manner. Indeed, we previously reported that rbr-2;jmjd-1.2 double mutants show similar levels of PVQ defects as the single mutants (Mariani et al, 2016), confirming that rbr-2 and jmjd-1.2 act in a common pathway regulating axon guidance. Altogether, these findings confirm that epigenetic factors are essential for the correct execution of developmental processes, providing novel insights into how neuronal development is achieved.…”
Section: Discussionsupporting
confidence: 62%
“…It is possible that altered actin dynamics counteract the effects of increased Hh signaling by regulating Hh trafficking and secretion. However, based on our previous findings that misexpression of actin regulators in PVQ neurons causes aberrant axon guidance (Mariani et al, 2016) and on our overexpression experiments in the wsp-1 mutant background, we favor a hypothesis (Fig. 5) in which JMJD-1.2 modulates the expression of Hh-related proteins in neuronal and hypodermal cells, which, after secretion, activate a signaling pathway controlling actin remodeling and axon guidance in target neurons.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations